Scientific and research competence of future ecology specialists - Soloshych, I. A. (Problems of Engineer-Pedagogical Education, 2018)
The study clarifies the definition of the concepts of «research competence» and «scientific-research competence» and determines the presence of the skills that provide the internal need of an individual for research activity in the process of studying at a higher educational establishment. The peculiar features of the research competence of future ecology specialists are distinguished, for example, non-algorithmicity, multi-functionality, universality, supramentality, multidimensionality, mobility, variability. The author outlined the content and functions of the research competence as an integral system of interrelated components, the structure of which includes motivational, value-based, methodological, cognitive, activity-based, communicative, reflexive, emotional-volitional components. The concept of the research competence of future environmentalists as an integrative and integral quality of an individual is grounded on the motivation- and value-based attitude to research work, which is in constant development, reflects the conscious readiness and ability to independently solve research (problem, educational, professional) tasks by applying methods of scientific research using the acquired knowledge, skills, competences and experience.